O som não se propaga no vácuo: o silêncio da crítica sobre a ficção científica no Brasil - Vollbrecht, Simone Caldas (2019)
This research has the purpose to present and discuss hypotheses for the silence of Brazilian criticism about the science fiction works. The position of national critics and academics on the science fiction genre will be examined, whether in relation to national or foreign authors. Using as corpus Dinah Silveira de Queiroz's “They shall inherit the Earth”, an analysis will be made of which elements are not being approached by the critics. Does Science fiction circulate only in the genre niches? The idea of this work came from examining the book Brazilian Science Fiction - Cultural Myths and Nationality in the Future Country, by the American researcher Mary Elizabeth Ginway. When looking for a national work that addressed the same theme, we found it much easier to find works by foreign critics about the genre, and even about national production, than nationally produced and published content. What would be the reason for such a vacuum? The literary production of the genre has taken place almost continuously since the late nineteenth century. However, the comment about it, the discussion, the debate, were absent regarding the literature. Such absence of production is not observed in the United States and Europe, countries in which it was possible to find research and criticism in large volume throughout the observed period. The research was conducted qualitatively. Comments and analysis were raised about the Brazilian critique and the current state of science fiction production in the country. If Science Fiction were a uniform genre, the identical behavior of criticism over the years would be explained in part. However, being so changeable of themes and approaches, and just being the same reception, it becomes of interest to identify why there is no evolution in positioning. Thus, the justification for this work is the existence of this vacuum between the rhythm and heterogeneity of publications of the genre in the country and the position of the Brazilian critic